2015
DOI: 10.1002/bit.25889
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Cel7A carbohydrate binding module and linker for reduced lignin inhibition

Abstract: Non-productive binding of cellulases to lignin inhibits enzymatic hydrolysis of biomass, increasing enzyme requirements and the cost of biofuels. This study used site-directed mutagenesis of the Trichoderma Cel7A carbohydrate binding module (CBM) and linker to investigate the mechanisms of adsorption to lignin and engineer a cellulase with increased binding specificity for cellulose. CBM mutations that added hydrophobic or positively charged residues decreased the specificity for cellulose, while mutations tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 21 publications
1
46
0
Order By: Relevance
“…Protein surface‐binding relationships evaluated in the present contribution suggest a controllable relationship between designed protein net charge and protein lignin binding capacity, consistent with recent efforts (Nordwald et al, ; Strobel et al, ). However, some low lignin‐binding designs had a positive net charge, showing that net charge alone is not sufficient to explain the entire dataset.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Protein surface‐binding relationships evaluated in the present contribution suggest a controllable relationship between designed protein net charge and protein lignin binding capacity, consistent with recent efforts (Nordwald et al, ; Strobel et al, ). However, some low lignin‐binding designs had a positive net charge, showing that net charge alone is not sufficient to explain the entire dataset.…”
Section: Discussionsupporting
confidence: 90%
“…Cellulases modified by succinylation to negatively charge the protein surface showed final higher conversion of Avicel in the presence of lignin compared with controls, suggesting that the electrostatic potential on a protein is also relevant for lignin‐mediated inactivation. Strobel et al investigated lignin adsorption behavior for a series of mutants of a family 1 CBM (Pfeiffer et al, ; Strobel et al, , ). Mutation of some residues lowered lignin adsorption without a corresponding loss of CBM1 binding to crystalline cellulose.…”
Section: Introductionmentioning
confidence: 99%
“…1 and 2 lignin. In the aliphatic region, the signals from -OCH3 at 55.8 ppm, β-O-4′ at around 72.3 ppm (Cα in β-O-4′), 85.2 ppm (Cβ in S type β-O-4′) and 60.1 ppm (Cγ in β-O-4′), β-5 at about 86.8 ppm (Cα) and Cγ in β-β′ at ~71.7 ppm (Samuel et al, 2010;Strobel et al, 2016) were readily assigned. structural information of lignin Fractions using 2D-hsQc nMr analysis HSQC is the most applied 2D NMR techniques for the structure determination of lignin samples with enhanced spectral resolution.…”
Section: Nmr Analysismentioning
confidence: 99%
“…Strong bindings of Trichoderma reesei CBH-I and EG-I to both cellulose and lignin were observed using quartz crystal microgravimetry (Martín et al, 2013). Other studies reported that the cellulose binding domain of the effluent enzyme played a significant role in the unspecific binding of cellulases to lignin (Palonen et al, 2004;Rahikainen et al, 2013;Strobel et al, 2015Strobel et al, , 2016. T. longibrachiatum, which are taxonomically separable from T. reesei, could also act as a potential cellulase candidate with high activities (Kubicek et al, 1996).…”
mentioning
confidence: 98%
“…Next, the CD cleaves the cellulose chains on the regions of low crystallinity to yield oligosaccharides and/or cellobiose [5]. The linker performs various functions, such as providing cold adaptation to cellulase of an Antarctic bacterium [4], separating the CD and CBM by a necessary distance, facilitating the dynamic adsorption of CBM on the substrate [6], acting as a molecular spring between two functional modules [6], and affecting the affinity of cellulase for lignin and cellulose [7]. Kont et al recently reported that the synergism between the CBM-linker and CD plays an important role in movement of the cellulose chain into the active site of the processive endoglucanase Cel7A from Trichoderma reesei [8].…”
Section: Introductionmentioning
confidence: 99%